Tubeless and Stentless Pyeloplasty - Haq, Amin ul; Khan, Isa (Journal of Postgraduate Medical Institute, 2011)
The aim of this study was to study cases of ureteropelvic junction obstruction undergoing openpyeloplasties without any stents and tubes. The techniques of operations designed in the present study were 88 anderson Hyne's Peyeloplasties, 22 Foley Y-V plasty, 24 Culp, Deweered and the rest of the 16 cases scardinoprince flap pyeloplasties. 142 (95%) of cases had improvement in symptoms and renal functions while there was failure in 8(5%) of cases. it is concluded that stents and nephrostomy tubes are not needed in patients except in those undergoing secondary repairs or having inflammation.